An exploratory study on factors influencing undergraduate students’ academic writing practices in Turkey - Bayyurt, Yasemin; ALTINMAKAS, DERYA (My University, 2019)
In EAP contexts, attaining a desired level of competence and fluency in academic writing is important for students majoring in English-medium undergraduate programs because their academic achievements are determined by the texts they produce in English. Undergraduate students in Turkey are observed to experience difficulties with academic writing as they try to accommodate their existing writing knowledge to the requirements of the new discipline-specific writing and learning situation of tertiary level education. Placing the students at the core of inquiry, the study explored factors influencing students' academic writing practices in English. The participants of the study were nineteen English major undergraduate students studying in Istanbul. The main data were obtained from background questionnaire, semi-structured interviews, document analysis, and were qualitatively analysed. The findings revealed that undergraduate writing is influenced by an array of interrelating educational and contextual factors: (1) the amount and nature of L1 and L2 pre-university writing instruction and experience, (2) students’ perceptions about academic writing and disciplinary-specific text genres, (3) prolonged engagement with the academic context and discourse, and (4) expectations of faculty members. The insights gained from the study provide important implications for reconceptualization of writing instruction in Turkey.
Keywords: Undergraduate writing; Academic writing; EAP; Turkey